The Degree to which Arabic Language Teachers in Saudi Arabia Possess Distance Learning Competencies - Al-Hersh, Misfer Saud Mubarak (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the degree to which Arabic language teachers in Saudi Arabia possess distance learning skills, and the study followed the descriptive approach, The study sample consisted of (120) teachers from schools in Bisha Governorate, Kingdom of Saudi Arabia. To achieve the objectives of the study, the researcher prepared a questionnaire consisting of (24) indicators distributed into three areas, namely: (teaching skills needed for distance learning, technical skills needed for distance learning, and assessment skills needed for distance learning), The results of the study showed that the arithmetic mean that the arithmetic averages and standard deviations of the degree to which Arabic teachers possess distance learning skills ranged between (3.58-3.60), where the field of teaching skills needed for distance learning ranked first with an arithmetic mean (3.60), With a medium degree of possession, and in the second rank, the field of technical skills needed for distance learning, with an arithmetic mean (3.59) and a medium degree of possession. Medium, and the total arithmetic mean of the tool was (3.59), with a medium possession degree, The results also showed that there were no statistically significant differences in the responses of the study sample about the degree to which Arabic language teachers possessed distance learning skills in teaching according to the variables of years of experience and learningal qualification. The researcher recommended the necessity of holding training courses for Arabic language teachers to provide them with the necessary cognitive, technical, technical and pedagogical skills to teach using technologies and techniques in teaching.